Effect of Hemolysis on Serum Markers of Liver Function - Bhattarai, Aseem; Thapa, Ranjana; Dubey, Raju Kumar; Raut, Mithileshwar; Niraula, Apeksha; Sharma, Vijay; Tuladhar, Eans Tara (Journal of Institute of Medicine Nepal, 2024)
Introduction Samples received in the laboratory are often rejected because of visible hemolysis. Every laboratory has protocols on whether to accept or reject hemolyzed samples based on tests ordered. The objective of the study was to observe and analyze the variations seen in association with hemolyzed samples in liver function test parameters and electrolytes measurement.MethodsThis cross-sectional observational study was carried out in 88 laboratory samples in the Clinical Biochemistry Laboratory. Hemolysis was induced by mechanical mixing. This study compared reported values of bilirubin, protein, albumin, aminotransferases (ALT and AST), alkaline phosphatase (ALP), gamma glutamyl transpeptidase (GGT), sodium and potassium between hemolyzed and non-hemolyzed samples.ResultsMean values of total bilirubin (TB) and direct bilirubin (TB), ALT, ALP, GGT and sodium (Na) were found to be significantly decreased post hemolysis (p